2020
DOI: 10.1159/000506156
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Polish version of the Drug-Use Disorders Identification Test

Abstract: Background: Substance use is a growing problem worldwide, and there is a great need to develop national policies addressing prevention and treatment of substance-use disorders (SUD). However, the lack of a commonly used, valuable diagnostic tool to assess the symptoms of SUDs precludes comparison of the prevalence of drug-use problems as well as the efficacy of policy strategies applied in different countries. This study was conducted to validate one of the commonly used scales the Drug Use Disorders Identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Several subsequent studies have echoed these results, and a literature review from 2015 concluded that the DUDIT performs “at a level that is at least comparable to, if not higher, than other drug screening instruments” ( Hildebrand, 2015 , p. 58). More recent research corroborates this conclusion (e.g., Basedow et al., 2021 ; Klimkiewicz et al., 2020 ; Sfendla et al., 2017 ).…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Several subsequent studies have echoed these results, and a literature review from 2015 concluded that the DUDIT performs “at a level that is at least comparable to, if not higher, than other drug screening instruments” ( Hildebrand, 2015 , p. 58). More recent research corroborates this conclusion (e.g., Basedow et al., 2021 ; Klimkiewicz et al., 2020 ; Sfendla et al., 2017 ).…”
Section: Introductionmentioning
confidence: 54%
“…According to Klimkiewicz et al. (2020) , the DUDIT is currently one of the most frequently recommended instruments for the screening of drug problems.…”
Section: Introductionmentioning
confidence: 99%
“…Similar properties are reported by the AU-DIT (r = 0.91) and DUDIT (r = 0.92), which indicates that the HUS is a tool of satisfactory reliability and can be compared with the methods commonly used so far. It is also worth noting that compared to other, less popular methods of measuring alcohol use intensity like the Alcohol Use Scale (r = 0.94), the HUS is relatively high [15,25,40].…”
Section: ■ Discussionmentioning
confidence: 99%
“…The Polish version of the questionnaire is highly reliable and Cronbach's α was 0.92. Receiver Operator Characteristic (ROC) analysis indicated a cut-off point of 7 with sensitivity of 0.929 and specificity of 0.974 [15,25].…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation